School in grandma's day - Weber, Valerie; Jenkins, Gloria (Carolrhoda Books, 1999)
Recalls what it was like to go to both a public and a Catholic school in Illinois in the 1940s.
Keywords: Jenkins, Gloria <1937-> -- Childhood and youth -- Juvenile literature; Geschichte 1900-2000; Alltag, Brauchtum; Geschichte; Catholic elementary schools -- Middle West -- History -- 20th century -- Juvenile literature; Catholic schools -- History -- 20th century; Elementary schools -- Middle West -- History -- 20th century -- Juvenile literature; School children -- Middle West -- Social life and customs -- 20th century -- Juvenile literature; Schools -- History -- 20th century; Middle West -- Social life and customs -- 20th century -- Juvenile literature